Semantic Web and Ontology applied to Web Services Discovery with QoS - Nakamura, Luis H. V.; Estrella, Julio C.; Santana, Marcos J.; Santana, Regina H. C. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2011)
This paper presents a study on the use of Semantic Web and Ontology created with the OWL (Web Ontology Language) to sort and selectWeb Services according to its Quality of Service (QoS) attributes. The focus of this paper is to evaluate the performance of this approach in accordance with some adopted parameters. To this end, two algorithms that use Semantic Web resources have been developed in order to make the discovery of appropriate Web Services in the ontology. At the end of this article, the results of a performance evaluation are presented and analyzed.